Use of Bactec MGIT 960 ParaTB system for the diagnosis of bovine paratuberculosis - TRANGADIA, B J; NAGMANI, K; MUKHERJEE, F; RANA, S K; SRINIVASAN, V A (The Indian Journal of Animal Sciences, 2016)
In the present study, Bactec MGIT 960 ParaTB system, a liquid culture system has been used to culture the Mycobacterium avium paratuberculosis (Map). Faecal, milk and serum samples were collected in separate sterile containers from 20 milking crossbred cows, aged above 4 years with a history of chronic diarrhea, weak body condition and weight loss. Five (25.0%, 5/20) animals reacted positively to single intra-dermal Johnin test. Four (20.0%, 4/20) samples each of serum and milk were positive by ELISA. The positive milk and serum samples belonged to the same individuals. Direct PCR could not detect Map DNA in any of the faeces/milk samples. However, 1 out of 20 faecal samples was tagged positive in system on day 19 post culture. Z-N staining, conventional IS900 PCR and real-time PCR confirmed these to be Map.